The Development of Islam as Civilization and Culture in Educational Management Development - Arif Nasution, Razman (Mudir : Jurnal Manajemen Pendidikan, 2023)
History of progress and setbacks achieved by Muslims in various fields, such as in the religious and general fields, science, culture, architecture, politics, government, war, education, economy and so on. Results of this research show that: 1) History of Islamic civilization is a description of Muslims life activities in the past which originate from Islamic values that developed in educational management. In Classical period, there was only one central government (Arab) and for several centuries this government was very strong. The role of Arab people was very dominant, as the consequnces all existing cultural expressions were expressed through Arabic, which ultimately had created a unified Islamic culture, which all of the culture was in Arabic. 2) To differentiate between Arab culture and Islamic culture, it can be viewed by using a concept. That in Islam, there is a collection of normative dogmas and Islam as historical reality. Apart from normative and historical concepts, in determining Arab culture and Islamic culture, it is also possible to use the concepts of Ushul and Furu'. 3) Among the historians there are different opinion regarding to when Islamic history began. The periods that commonly used in the history of Islamic civilization are divided into three periods, namely the classical period, the medieval period and the modern period, all of them are used as references in the development of Islamic education management.